Online reciprocal peer tutoring approach in Facebook: measuring students' critical thinking - Zulkifli, Nurul Nadwa; Abd Halim, Noor Dayana; Yahaya, Noraffandy; van der Meijden, Henny; Mohd Zaid, Norasykin; A Rashid, Ana Haziqah; Hashim, Suhaizal (International Association of Online Engineering, 2021)
Critical thinking skills are one of essential employability skills for graduates when entering the workforce. The lack of critical thinking skills among Malaysian graduates is a concern as these skills are important for success in the 21st century. Therefore, this paper aims to study the effects of online reciprocal peer tutoring (RPT) through Facebook discussion on students’ critical thinking. In this study, the online RPT approach in Facebook was used to nurture students to think critically. In RPT, the tutor role is switched between participants in each task, giving equal opportunities to all learners to benefit from the tutor and tutee role. This approach was integrated into their learning for 4 weeks to increase students' critical thinking. During the learning process, they need to involve in 4 critical thinking tasks based on Bloom's taxonomy. 29 undergraduate students from the school of education, Faculty of Social Sciences and Humanities at Universiti Teknologi Malaysia completed the validated instrument, Watson-Glaser Critical Thinking Appraisal test (inference, assumption, deduction, interpretation, evaluation arguments) before and after the treatment. The findings show that it is significantly different in making inference (Z=-3.85, p=.000<*.05) and deduction (Z=-3.627, p=.000<*.05) criterion in post-test. These revealed that students who engaged in the online RPT environment showed positive improvements in those criteria in critical thinking after the treatment. In conclusion, students’ critical thinking can be taught to students using Facebook with active learning strategies such as online RPT.